Artificial Intelligence Auditing: Embracing the Disruption. Are You Prepared? - Eka Pratiwi, Yanna; Lastianti, Siwidyah Desi; Wijayanto, Indra; Hidayat, Ujang Syaiful; Susanto, Iwan Wahyu (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This article investigates the growing presence of artificial intelligence (AI) in the accounting industry, as well as its possible impact on the auditing profession. We investigate 29 papers from 18 journals using a semi-sytematic literature review. While AI provides benefits such as increased efficiency, efficacy, and decision-making, it still requires human oversight, particularly in areas like as fraud detection and communication with in-house accounting. The complexities of human judgment, as well as the requirement for auditor discretion, remain critical. Furthermore, because it can be challenging to use AI in auditing methods in Indonesia, where infrastructure for data analysis and verification is typically reliant on physical documents, auditors can still keep their jobs.